2013
DOI: 10.4236/aid.2013.31003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Human Papillomavirus and Oesophageal Squamous Cell Carcinoma in China—A Review of the Evidence

Abstract: Background: China has one of the highest incidence rates of oesophageal cancer in the world. The role of human papillomavirus (HPV) has been extensively researched in oesophageal squamous cell carcinoma (OSCC) with indeterminate results. The majority of these studies have been conducted in the Chinese population. Evidence for a definitive HPV-OSCC association could potentially support prophylactic vaccination in target populations, highlighting the need for ongoing investigation. The aim of this review is to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
(84 reference statements)
0
4
0
Order By: Relevance
“… *Some of the data included in the table have been described in one of our previous publications. 10 †All ORs in this table are unadjusted and have been calculated using the Epi Info programme, except for two studies (Cao et al and Gao et al ), where the authors of the respective articles provided calculated adjusted ORs. ‡One paper (Li et al ) has an OR deemed to be incalculable as a result of one or more of the four components for OR calculation being a zero value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… *Some of the data included in the table have been described in one of our previous publications. 10 †All ORs in this table are unadjusted and have been calculated using the Epi Info programme, except for two studies (Cao et al and Gao et al ), where the authors of the respective articles provided calculated adjusted ORs. ‡One paper (Li et al ) has an OR deemed to be incalculable as a result of one or more of the four components for OR calculation being a zero value.…”
Section: Methodsmentioning
confidence: 99%
“… 23 Despite the high overall rate of HPV detection in OSCC in China, different studies have found a geographical variation in the rates of HPV in OSCC, possibly a real variation, but possibly in part reflecting the different detection methods used. 19 10 However, a recent study found no significant impact of the different detection methods on the detection rates of HPV. 23 This complexity and the high disease burden of OSCC in China highlight the need to better understand the relationship of HPV to OSCC in China.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increased risk factor in this case as indicated by Cheng and Day (22) may come as a consequence from a direct contact of the potential carcinogen with the epithelium, some existing transport facilitating mechanism, or derived from compounds that increase the cell turnover in the epithelial cells. Albeit yet a controversial topic, there have been also studies trying to correlate the occurrence of HPV infections and ESCC, though results showed an elevated degree of variation that did not yield a clear association between the viral infection and the development of the disease (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%